Microplastics combined with tetracycline in soils facilitate the formation of antibiotic resistance in the Enchytraeus crypticus microbiome. (September 2020) - Ma, Jun; Sheng, G. Daniel; O'Connor, Patrick
Abstract: Growing evidence suggests that microplastics can adsorb antibiotics and may consequently exacerbate effects on the health of exposed organisms. Our current understanding of the combined effects of microplastics and antibiotics on antibiotic resistance genes (ARGs) in soil invertebrates is limited. This study aimed to investigate changes in the microbiome and ARGs in Enchytraeus crypticus following exposure to a soil environment that contained both microplastics and antibiotics. Tetracycline (TC), polyamide (PA) and polyvinyl chloride (PVC) were used to construct microcosms of polluted soil environments (TC, PA, PVC, PA+TC, PVC+TC). The differences in microbiomes and ARGs were determined by bacterial 16S rRNA gene amplicon sequencing and high throughput quantitative PCR. The results show that compared with the Control or microplastics alone treatments, TC was significantly accumulated in E. crypticus when exposed to TC alone or in combination with microplastics ( P  < 0.05), but there were no significant differences about TC accumulation between TC, PA+TC, and PVC+TC treated E. crypticus ( P  > 0.05). Microplastics and TC significantly disturbed the microbial community, and decreased the microbial alpha diversity of E. crypticus ( P  < 0.05). However, there were no significant differences between TC, microplastics and their combined exposure treatments, and no toxic synergies on the diversity of E. crypticus microbiome between tetracycline and microplastics in soil environment. All the treatments increased the diversity of ARGs in E. crypticus (39–49 ARGs vs. 25 ARGs of control). In particular, treatments combining PVC and TC or PA and TC exposure resulted in greater ARGs abundance than the treatments when E. crypticus was exposed to PVC, PA or TC alone. These results add to our understanding of the combined effects of microplastics and antibiotics on the ARGs and microbiome of soil invertebrates. Graphical abstract: Image 1 Highlights: Tetracycline and microplastics disturbed the microbial community in E. crypticus. Tetracycline and microplastics decreased the microbial diversity of E. crypticus . Tetracycline and microplastics facilitated the incidence of ARGs in E. crypticus. Abstract : Soil combined pollution by different microplastics with tetracycline increase the incidence of ARGs in the Enchytraeus crypticus microbiome.